The EFL Learners’ Listening Comprehension Through Western Song and The Strategies for Improvement - Pratiwi samad; Nirma Paris (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The Purpose of this research was to determine and to describe the students’ difficulties in comprehending the western song and their strategies used in improving the ability by the EFL learners of Pohuwato University. The method used in this research was a qualitative descriptive and took the first semester of English Department of Pohuwato University as the subject of this research. The researcher used purposive sampling technique in determining the subject and obtaining the data by used interview and observation as the instrument. The result shows that the EFL learners of Pohuwato University had the difficulties in listening the western song. They were didn’t understand the topic of the song, lack of vocabularies and difficult to comprehend the whole song while in comprehending the western song, the EFL learners of Pohuwato University applied four strategies. They were preparing strategy, paying attention strategy and note taking vocabularies in order to understand the whole song message and ideas of the topic from the song.